2016
DOI: 10.1016/j.neuro.2016.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Synergy as a new and sensitive marker of basal ganglia dysfunction: A study of asymptomatic welders

Abstract: Background Multi-digit synergies, a recently developed, theory-based method to quantify stability of motor action, are shown to reflect basal ganglia dysfunction associated with parkinsonian syndromes. In this study, we tested the hypothesis that multi-digit synergies may capture early and subclinical basal ganglia dysfunction. We chose asymptomatic welders to test the hypothesis because the basal ganglia are known to be most susceptible to neurotoxicity caused by welding-related metal accumulation (such as ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 74 publications
2
25
0
Order By: Relevance
“…The application of principles of sensory-motor integration in laboratory settings is not new, but recent technical developments have caused these techniques to become more sensitive and reliable 15 17 . For example, the use of these principles has allowed the detection of subtle balance impairments in long-term mTBI survivors 18 and abnormalities in coordination of multi-finger force production and control in Parkinson’s disease 19 , 20 . Studies utilizing indices of oculomotor performance have been no exception; however, its application to cases of mTBI has yielded conflicting outcomes 8 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The application of principles of sensory-motor integration in laboratory settings is not new, but recent technical developments have caused these techniques to become more sensitive and reliable 15 17 . For example, the use of these principles has allowed the detection of subtle balance impairments in long-term mTBI survivors 18 and abnormalities in coordination of multi-finger force production and control in Parkinson’s disease 19 , 20 . Studies utilizing indices of oculomotor performance have been no exception; however, its application to cases of mTBI has yielded conflicting outcomes 8 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Note that patients with various neurological disorders show significant impairments of action stability (Latash and Huang 2015). For example, this is true for patients with Parkinson’s disease at very early stages of the disorder when they are tested on optimal medication (Park et al 2012) and even for healthy persons who are at high risk for basal ganglia-related disorders, such as professional welders (Lewis et al 2016). Studies in patients with multiple sclerosis have shown a significant reduction in the synergy index (Δ V ), which was due to a nearly two-fold drop in the seemingly irrelevant component of inter-trial variance ( V UCM ), whereas the component that affected performance ( V ORT ), showed no difference between the patients and control subjects (Jo et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ASAs are reduced and decreased in magnitude in patients with both cortical and subcortical disorders (Park et al 2012; Jo et al 2016). Indices of synergic control are sensitive to very early stages of PD; they can be seen in the apparently non-involved hands of patients at HY stage-I (Park et al 2012, 2014) and even in asymptomatic persons at elevated risk for parkinsonism, such as professional welders (Lewis et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Second, the approach has proven its specificity to subcortical neurological disorders (reviewed in Latash and Huang 2015) in support of the idea of distributed processing modules involving loops through the cerebellum and the basal ganglia (Houk 2005). Third, the approach is highly sensitive to very early stages of disorders (such as PD subjects in HY stage-I, Park et al 2012, 2013, 2014) and even to subclinical changes in persons at elevated risk for parkinsonism (Lewis et al 2016). Other mentioned approaches are typically computational, use behavioral indices with no clear links to physics and physiology, and/or are not as sensitive to disease-related changes.…”
Section: Discussionmentioning
confidence: 99%